CONCRETE WASTE AS COARSE AGGREGATE IN CEMENTITIOUS MATRICES- REVIEW - Jordane Gabriele Santos Alves; Laura Viana de Melo; Rodrigo Dias Bedetti; White José dos Santos (Mix Sustentável)
The aggregates present in concrete composition are non-renewable resources obtained through multiple mining or extraction innovations, which cause significant damage to nature. At the same time, the increasing generation of amounts of concrete waste is a reality. Most construction and demolition waste is quimically inert and non-hazardous, however, it represents a problem when it is disposed of, since landfills have their useful life shortened due to the large volume of this type of disposal, which is, in most cases, sometimes landfilled. Therefore, this article’s objective is to survey the caracteristics of this waste and concrete properties produced using it as coarse aggregate. A systematic literature review is carried out and the feasibility of applying hardened concrete waste as recycled aggregate in cement matrices is discussed. It is observed that composites with recycled aggregates reached values close to conventional concrete, being within usable ranges based on normative references, such as the properties of compressive strength, water absorption, density and modulus of elasticity. Therefore, it is viable to incorporate recycled aggregates in partial replacement of conventional aggegates.